Pengaruh Celebrity Worship terhadap Psychological Well-Being pada Penggemar K-Pop di Kota Bandung - Cherta Alifia El Diva; Yanuvianti, Milda (Bandung Conference Series: Psychology Science, 2024)
Abstract. Bandung, as one of the cities in Indonesia, is an area that is fond of K-Pop music (1). However, liking K-Pop idols often triggers celebrity worship among fans which can lead to symptoms of depression, anxiety, dysfunction and overthinking which indicate poor psychological health (2). Psychological well-being can decrease or be low which can be caused by celebrity worship. This study aims to determine the effect of celebrity worship on psychological well-being in K-Pop fans in Bandung City. This study uses a quantitative approach with 392 respondents who are individuals who live in Bandung City, aged 20-30 years, and K-Pop fans. The measuring instrument used Celebrity Attitude Scale (CAS) has been adapted into Indonesian by Efathania (3) to measure celebrity worship and Ryff's Psychological Well-Being Scale (RPWB) has been adapted into Indonesian by Rachmayani and Ramdhani (4) to measure psychological well-being. From the results of data analysis, there is a significant influence of celebrity worship variables on psychological well-being in K-Pop fans in Bandung City of 4.4% with a significance value of .000 <.1. The effect of celebrity worship on psychological well-being in K-Pop fans in Bandung City is relatively small. Abstrak. Kota Bandung sebagai salah satu kota di Indonesia, menjadi daerah yang menggemari musik K-Pop (1). Namun, menyukai idol K-Pop kerap memicu celebrity worship di kalangan penggemar yang dapat memunculkan gejala depresi, kecemasan, disfungsi dan overthinking yang menunjukkan tidak baiknya kesehatan psikologis (2). Psychological well-being dapat menurun atau rendah yang dapat disebabkan oleh celebrity worship. Penelitian ini bertujuan untuk mengetahui pengaruh celebrity worship terhadap psychological well-being pada penggemar K-Pop di Kota Bandung. Penelitian ini menggunakan pendekatan kuantitatif dengan responden berjumlah 392 orang yang merupakan individu yang berdomisili di Kota Bandung, berusia 20-30 tahun, dan penggemar K-Pop. Alat ukur yang digunakan Celebrity Attitude Scale (CAS) telah diadaptasi ke dalam bahasa Indonesia oleh Efathania (3) untuk mengukur celebrity worship dan Ryff’s Psychological Well-Being Scale (RPWB) telah diadaptasi ke dalam bahasa Indonesia oleh Rachmayani dan Ramdhani (4) untuk mengukur psychological well-being. Dari hasil analisis data, terdapat pengaruh variabel celebrity worship terhadap psychological well-being pada penggemar K-Pop di Kota Bandung yang signifikan sebesar 4.4% dengan nilai signifikasinya, yaitu .000<.1. Pengaruh celebrity worship terhadap psychological well-being pada penggemar K-Pop di Kota Bandung terbilang kecil.